Gender Variation, subject dispersion and citation impact in dental research: A bibliometric analysis of publications from 2009-2021 - Lubna Alkadi; Ikram Ul Haq; Wafa Allhaidan; Jumanah Almusa; Abdulsalam Alshammari (Elsevier, 2024)
Aim: This study probed into the gender variation, subject dispersion and citation impact of dental research with an objective to highlight the increasing influence of female authors in the field of dentistry. Methodology: The research employed bibliometric techniques to highlight gender variation in dental research as demonstrated in the Saudi Dental Journal (SDJ), over a period of thirteen years, 2009-2021. The examination comprised SDJ publications indexed in PubMed, with citation data extracted from Google Scholar on July 2023. The analysis encompassed the progressive growth of papers, authors, and citations, the gender distribution of authors, the co-authorship structure, subject dispersion, and collaboration patterns based on affiliation, both national and international. Results: 625 SDJ publications were identified in the PubMed database from 2009 to 2021. There was a notable rise in the volume of papers and the number of authors per year. The citation impact analysis revealed that these 625 papers achieved an average of 26 citations each. Remarkably, the representation of female authors increased from 0.47 to 2.23 authors per paper during the study period. The authorship pattern largely showed single-authorship, closely followed by a three-author pattern. Almost half the papers (48%) were a collaboration between male and female authors, with female authors solely producing about 15% of papers.The topological classification of papers revealed that the most considerable number of papers were on Periodontics, with the least number focusing on Oral and Maxillofacial Surgery. Female authors prominently contributed to Pediatric Dentistry and Periodontics papers. Conclusion: The study illustrates an encouraging trend of heightened female authorship in dental research over the years. Their increasing engagement not only enriches the academic diversity but also impacts the progressive evolution of dental science, contributing to a more inclusive and balanced society.